2008
DOI: 10.18388/abp.2008_3216
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of O-specific polysaccharide structure of symbiotically defective Mesorhizobium loti mutant 2213.1 derived from strain NZP2213.

Abstract: Mesorhizobium loti mutant 2213.1 derived from the wild-type strain NZP2213 by Tn5 mutagenesis showed impaired effectiveness of symbiosis with the host plant Lotus corniculatus (Turska-Szewczuk et al., 2007 Microbiol Res, in press). The inability of lipopolysaccharide (LPS) isolated from the mutant 2213.1 strain or de-O-acetylated LPS of the parental cells to inactivate phage A1 particles implicated alterations in the LPS structure. The O-specific polysaccharide of the mutant was studied by chemical analyses al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In the previous report, it was shown that the NZP2213.1 mutant is resistant to lysis of phage A1 due to the changed LPS structure, and fully O -acetylated wild-type O-PS was indicated to be a receptor for the phage [ 19 ]. In the present study, the complemented NZP2213.1(pBGoatB) strain subjected to the action of phage A1 was lysed similarly to the WT strain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous report, it was shown that the NZP2213.1 mutant is resistant to lysis of phage A1 due to the changed LPS structure, and fully O -acetylated wild-type O-PS was indicated to be a receptor for the phage [ 19 ]. In the present study, the complemented NZP2213.1(pBGoatB) strain subjected to the action of phage A1 was lysed similarly to the WT strain.…”
Section: Resultsmentioning
confidence: 99%
“…The molar ratio of the main sugars building the O-chain i.e., 6-deoxytalose (6dTal p ) and 2- O -methyl-6-deoxytalose (2-OMe-6dTal p ), in relation to N -acetylquinovosamine (QuipNAc), which is a sugar of the outer core tetrasacharide [ 19 , 21 ], was ~33:1 and 15:2, in lipophilic S-LPS of the WT and mutant NZP2213.1 strains, respectively. In turn, the molar ratio of 6dTal p and 2-OMe-6dTal p estimated at ~27:1.9 in the O-PS of the complemented NZP2213.1(pBGaotB) strain indicated the restoration of the WT proportion of sugars ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…W preparatach polisacharydowych tych bakterii zidentyfikowano także heksozy (Man, Gal), O-metyloheksozy, heptozę i jej metylową pochodną, aminocukry, kwasy uronowe oraz podstawniki niecukrowe np. grupy acetylowe [59,60,46,[61][62][63][64][65].…”
Section: Rizobiowe Polisacharydy O-swoisteunclassified